Gender, Trauma and Power in China Keitetsi's La petite fille à la Kalachnikov: Ma vie d'enfant soldat. Issue 4 (2nd October 2022) - Messay, Marda
ABSTRACT: This article focuses on China Keitetsi's memoir La petite fille à la Kalachnikov (2004) in which she describes her early childhood in Uganda as well as her experiences as a female child soldier in the Ugandan National Resistance Army (NRA) under Yoweri Museveni from 1985 to 1995. First, I briefly explore the intended objectives of her text as a crucial therapeutic step and a political act. Second, I examine her narration of her early childhood in which she evokes Ugandan women's lack of social and economic power and denounces the intimate and sexual violence that girls and women experience. Lastly, I study how her narration of her experiences as a female child soldier provides invaluable insight into the complex experiences of female child soldiers, by showing not only the empowerment they feel as soldiers but also the sexual violence they experience as females and its effects on their psyche. Through my analysis, I demonstrate how Keitetsi not only exposes the trauma she experienced but also condemns the socio-cultural and political structures that victimised her as a girl and later as a female child soldier. Keitetsi's memoir generates important reflections on gender and power.